Laser thermotherapy target head with heat-conducting material, heat-conducting material and preparation method thereof

By using a composite thermally conductive material of WAVBO2@SiO2, carbon nanotubes, polymer matrix and metal foam, combined with a passive temperature control system, the problems of inaccurate temperature monitoring, electrical safety risks and small treatment area in laser thermotherapy technology have been solved, achieving miniaturization, safety and cost-effectiveness of the target head.

CN122465295APending Publication Date: 2026-07-28SOUTH CHINA UNIV OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610521715.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-07-28

AI Technical Summary

Technical Problem

Existing laser thermotherapy technology lacks reliable real-time temperature monitoring methods, poses electrical safety risks, has a small treatment area, and traditional point light source irradiation mode is difficult to achieve uniform, large-area conformal thermotherapy. High equipment costs or complex structures mean that the target head cannot be used once.

Method used

A composite thermally conductive material consisting of WAVBO2@SiO2, carbon nanotubes, a polymer matrix, and metal foam is used in conjunction with a passive temperature control system. This system achieves closed-loop active temperature regulation by detecting the power of reflected laser light, and provides passive protection when the temperature exceeds a threshold to prevent overheating.

Benefits of technology

It achieves miniaturization and passive insulation of the target, avoids electrical safety risks, increases the thermotherapy area, improves treatment efficiency and safety, reduces medical costs, and adapts to the thermotherapy needs of tumors in different locations and types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122465295A_ABST
    Figure CN122465295A_ABST
Patent Text Reader

Abstract

This invention relates to the field of laser thermotherapy target technology, and particularly to a laser thermotherapy target with a thermally conductive material, the thermally conductive material, and a method for preparing the same. The thermally conductive material comprises W... A V B O2@SiO2, carbon nanotubes, a polymer matrix, and a metal foam, with an adjustable tungsten doping ratio, induces a reversible phase transition at a specific temperature. Preparation involves first synthesizing W through hydrothermal, annealing, modification, and coating processes. A V B O2@SiO2 powder is then used to enhance interfacial bonding by acidifying and amination of carbon nanotubes. Finally, it is composited with a polymer solution, filled into a metal foam framework, and cured. A laser thermotherapy target head constructed based on this material utilizes its thermally induced phase change for passive temperature limitation. Real-time monitoring of reflected light power via a dual-cavity fiber optic cable, combined with closed-loop control by a data processor, enables precise and safe active temperature control. This target head combines the advantages of passive safety, uniform thermal field, compact structure, and low cost, making it suitable for minimally invasive thermotherapy of diseases such as tumors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser thermotherapy target technology, and particularly to a laser thermotherapy target with a thermally conductive material, the thermally conductive material, and the preparation method thereof. Background Technology

[0002] Existing research indicates that effective necrosis of tumor tissue can occur under continuous exposure at 43-44℃ for 30-60 minutes or at 45-48℃ for a short period, while causing minimal damage to normal tissue. However, current laser thermotherapy technology still faces significant challenges when applied to tumors in deep organs. Currently, domestic laser thermotherapy equipment (such as for the treatment of intervertebral discs or prostate cancer) mainly achieves treatment through laser vaporization or cutting. However, in tumor treatment, direct application of high-power lasers to vital organs can easily cause irreversible damage to adjacent tissues.

[0003] In terms of temperature control technology, Medtronic's Visualase system relies on numerical simulation to predict temperature and lacks a real-time temperature measurement device. It uses high-cost sapphire material to reduce the risk of localized overheating. Monteris Medical's NeuroBlate system, while incorporating active thermocouples for temperature monitoring, increases electrical safety risks and raises the target diameter to 3.3 mm, increasing the risk of trauma. Chinese patent publication CN108671416A proposes a laser thermotherapy target based on graphite-based composite thermally conductive materials. While it improves heat deposition, it still relies on direct irradiation from a fiber optic point source, resulting in a very small effective thermal contact area (approximately 0.0087 mm). 2 This makes it difficult to achieve effective coverage of large tumors.

[0004] Therefore, existing technologies suffer from the following prominent problems: First, there is a lack of reliable and safe real-time temperature monitoring methods; existing solutions either rely on idealized models or introduce active electrical components, which pose safety risks. Second, the treatment area is small, and traditional point light source irradiation modes cannot achieve uniform, large-area conformal hyperthermia. Third, the equipment is expensive, either due to the use of costly materials or the complexity of the structure, which prevents the target head from being used in a single application. These shortcomings collectively limit the safety and effectiveness of laser hyperthermia in tumor treatment. Summary of the Invention

[0005] In order to address the technical deficiencies mentioned in the background section, the present invention aims to provide a laser thermotherapy target with a thermally conductive material, the thermally conductive material, and a method for preparing the same, so as to solve the above problems.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A thermally conductive material comprising the following components: W A V BO2@SiO2, carbon nanotubes, polymer matrix and metal foam, where 0≤A<B<1.

[0007] Specifically, it includes the following components by mass: W A V B O2@SiO2 6~9 parts, carbon nanotubes 0.5~1.5 parts, polymer matrix 58~61 parts, metal foam 30~32 parts.

[0008] Specifically, the polymer matrix is ​​polymethyl methacrylate.

[0009] Specifically, the metal foam is copper foam with a pore density of 5-20 PPI.

[0010] Specifically, it includes the following steps: S1. Carbon nanotubes are acidified to obtain acidified carbon nanotube powder. S2. The acidified carbon nanotube powder is subjected to amination treatment to obtain amination-modified carbon nanotube powder. S3, W A V B O2@SiO2 powder, the amino-modified carbon nanotube powder, polymer matrix raw materials and organic solvent are mixed to obtain a mixed slurry; S4. The mixed slurry is combined with a metal foam skeleton and cured to obtain the thermally conductive material.

[0011] Specifically, in step S1, the acidification treatment is as follows: carbon nanotubes are dispersed in a mixed acid, ultrasonically treated for 0.5-2 hours, stirred at room temperature for 12-36 hours, and then washed and dried to obtain acidified carbon nanotube powder; the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of (2~4):1.

[0012] Specifically, in step S2, the amination treatment includes: S2a. The acidified carbon nanotube powder is mixed with thionyl chloride and reacted at 50-70°C for 18-30 hours. S2b, followed by the addition of a polyamine compound, reacted at 80-120℃ for 18-30 hours, and after washing and drying, amination-modified carbon nanotube powder was obtained.

[0013] Specifically, in step S3, the organic solvent is one or more of acetone, N,N-dimethylformamide, and tetrahydrofuran; the polymer matrix raw material is polymer powder or polymer precursor.

[0014] Specifically, in step S4, the curing is carried out under a vacuum or inert atmosphere, the curing temperature is 40-80℃, and the curing time is 12-48 hours.

[0015] Specifically, prior to step S1, the preparation of W is also included. A V B Step S0 of O2@SiO2 powder preparation specifically includes: S01. Dissolve the vanadium source and the tungsten source in water to obtain a mixed solution; S02. Add a reducing agent to the mixed solution and stir until homogeneous; S03. The mixture obtained in step S02 is subjected to a hydrothermal reaction to obtain a precursor precipitate; S04. The precursor precipitate is washed, dried and annealed to obtain WAVBO2 powder. S05, regarding the W A V B O2 powder is modified with an aminosilane coupling agent on its surface. S06, W after surface modification A V B Using O2 powder as the core, a SiO2 shell is coated onto its surface via the sol-gel method to obtain W. A V B O2@SiO2 powder.

[0016] Specifically, in step S01, the vanadium source is one of ammonium metavanadate, vanadium pentoxide, or vanadium oxalate; the tungsten source is one of ammonium metatungstate, tungstic acid, or tungsten trioxide; and the molar ratio of the vanadium source to the tungsten source is (200~12000):(0~1).

[0017] Specifically, in step S02, the reducing agent is one of oxalic acid, hydrazine hydrate, or ascorbic acid.

[0018] Specifically, the hydrothermal reaction temperature is 180-280℃, and the reaction time is 12-36 hours.

[0019] Specifically, in step S04, the annealing process is carried out in an inert atmosphere or vacuum, the annealing temperature is 400-600℃, and the annealing time is 4-8 hours.

[0020] Specifically, in step S05, the surface aminosilane coupling agent modification is carried out under acidic conditions, with a pH value of 3-5, a reaction temperature of 50-70℃, and a reaction time of 4-8 hours.

[0021] Specifically, in step S06, the sol-gel method is carried out under alkaline conditions, using tetraethyl orthosilicate as the silicon source, with a reaction pH of 8-10, a reaction temperature of 40-60℃, and a reaction time of 8-16 hours.

[0022] A laser thermotherapy target head, comprising: The target head body contains the aforementioned heat-conducting material. A dual-cavity optical fiber, optically connected to the target head body, includes a laser incident channel for transmitting emitted laser light and a laser reflection channel for receiving reflected laser light. A laser emitter is optically connected to the laser incident channel; An optical power meter, optically connected to the laser reflection channel, is used to detect the power of the reflected laser. A data processor, electrically connected to the laser emitter and the optical power meter, is used to control the output power of the laser emitter based on the reflected laser power detected by the optical power meter.

[0023] Beneficial effects: 1. This invention constructs a passive temperature control system combining active and passive methods, achieving miniaturization of the target head while ensuring safety. Based on the thermally induced phase change characteristics of the material, closed-loop active temperature control can be achieved by detecting the reflected laser power. Furthermore, when the temperature exceeds a preset threshold, the material itself provides passive protection through high reflectivity, fundamentally eliminating the risk of overheating. This solution completely eliminates active electrical components, achieving full passive insulation of the part penetrating the human body. This not only completely eliminates electrical safety risks but also successfully reduces the target head diameter to approximately 1 mm, significantly reducing patient trauma.

[0024] 2. This invention achieves a transformation from a point heat source to a surface heat source, effectively increasing the thermotherapy area and avoiding local overheating. By using a target head made of high thermal conductivity composite material and medical-grade stainless steel, the laser energy transmitted through the optical fiber can be rapidly absorbed and uniformly dispersed throughout the target head volume, and then applied to the tissue through heat conduction. This solves the inherent defects of traditional fiber optic point light sources, such as small irradiation area, highly concentrated energy, and a high risk of local burns. It enables uniform and conformal thermotherapy of larger tumor tissues, thereby improving treatment efficiency and safety.

[0025] 3. The adaptive temperature control material of this invention has an adjustable temperature threshold, enabling flexible adaptation to clinical treatment needs. By adjusting the doping ratio of tungsten in the material, its phase transition temperature can be precisely set, thereby stabilizing the core temperature of hyperthermia within a preset optimal treatment window. This programmable temperature characteristic allows the same technology platform to adapt to the differentiated hyperthermia requirements of different sites and types of tumors, enhancing the universality and clinical applicability of the technology.

[0026] 4. This invention features a simple structure and low material costs, facilitating single-use and reducing overall medical costs. The main materials used in the target head are conventional chemical and medical materials, with mature and simple manufacturing processes, avoiding the use of expensive components such as sapphire. This design allows the entire target head to be used single-use at low cost, eliminating the risk of cross-infection and removing complex disinfection and maintenance procedures, thus reducing overall medical costs and the burden on patients. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the structure of the laser thermotherapy target head of the present invention; Figure 2 This is a schematic cross-sectional view of the main body of the laser thermotherapy target head of the present invention; Figure 3 This is a graph showing the relationship between the temperature of the thermally conductive material and the reading of the optical power meter according to the present invention; Figure 4 The diagram shows a numerical simulation model, where the needle represents the laser thermotherapy target and the sphere represents simulated tumor tissue. Figure 5 The temperature curves are compared between materials exhibiting adaptive temperature control properties under constant laser irradiation of 0.1W, 0.3W, and 0.5W for 5 minutes. Figure 6 The graph shows the temperature curves at the highest point on the target surface under constant laser irradiation of 0.1W, 0.3W and 0.5W for 5 minutes, comparing whether the material has adaptive temperature control properties. Figure 7 This is a graph showing the relationship between the temperature of the thermally conductive material and the reading of the optical power meter in Example 1; Figure 8 This is a graph showing the relationship between the temperature of the thermally conductive material and the reading of the optical power meter in Example 2; Figure 9 This is a graph showing the relationship between the temperature of the thermally conductive material and the reading of the optical power meter in Example 3.

[0028] Figure reference numerals: 1. Target head body; 2. Dual-cavity fiber; 3. Fiber optic coupler; 4. Fiber optic cable; 5. Optical power meter; 6. Laser emitter; 7. Data cable; 8. Data processor; 9. Thermal conductive material; 10. Laser reflection channel; 11. Laser incident channel. Detailed Implementation

[0029] This invention provides a laser thermotherapy target head with a thermally conductive material, the thermally conductive material, and a method for preparing the same. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0030] In the description of this application, it should be understood that the orientation descriptions, such as up, down, front, back, left, right, etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting the present invention.

[0031] like Figure 1-2As shown, this application discloses a disposable laser thermotherapy target head, including a target head body 1, a dual-cavity optical fiber 2, an optical fiber coupler 3, an optical fiber 4, an optical power meter 5, a laser emitter 6, a data cable 7, a data processor 8, a thermally conductive material 9, a laser reflection channel 10, and a laser incident channel 11; the target head body 1 is a hollow medical stainless steel cylindrical tube, and the front end of the body 1 is a spherical guide. The thermally conductive material 9 is embedded in the target head body 1.

[0032] The dual-cavity fiber 2 is constructed by taper-jointing the front ends of two 105μm or 125μm fibers into a single unit, aiming to minimize the fiber diameter and match the dimensions of the target head body 1. After taper-jointing, the front end of the dual-cavity fiber 2 is coated with a medical-grade PVC coating. The dual-cavity fiber 2 is then fixed to the target head body 1 using medical adhesive and an interference fit. At the untapered rear ends of the dual-cavity fiber 2, a fiber coupler 3 is fused to each other.

[0033] The fiber optic coupler 3 is an FC fiber optic coupler, which can be easily installed and removed by simply turning the plug-in knob. Because the laser thermotherapy target head of this application is for single use, before each use, the fiber optic coupler 3 at its rear end is connected to the fiber optic coupler 3 that connects to the laser transmitter 6 and the optical power meter 5, thus connecting the laser transmitter 6 and the optical power meter 5 and achieving the target function.

[0034] Fiber 4 is made of 105μm or 125μm fiber, and its front end is connected to fiber coupler 3, which is connected to dual-cavity fiber 2. The rear end of fiber 4 is connected to laser emitter 6 and optical power meter 5, respectively.

[0035] The optical power meter 5 transmits laser light through optical fiber 4 and dual-cavity optical fiber 2 and monitors the power of the laser light reflected by the heat-conducting material 9 in real time.

[0036] The laser emitter 6 emits laser light through the optical fiber 4 and the dual-cavity optical fiber 2 to the heat-conducting material 9.

[0037] Data cable 7 is an RS232 data cable used to connect the data processor to the laser emitter and optical power meter.

[0038] The data processor 8 is a desktop computer with dedicated PLC control software. It acquires the reading of the optical power meter 5 in real time through the data cable 7, performs data conversion internally, calculates the real-time temperature of the heat-conducting material 9, and adjusts the laser emission power of the laser emitter 6 in real time according to the real-time temperature of the heat-conducting material 9 to ensure that the temperature of the heat-conducting material 9 remains constant. Figure 3 The image shows the reflectivity of one of the thermally conductive materials 9, prepared with a specific formulation, under constant 0.1W laser irradiation, and the corresponding optical power meter readings as a function of its temperature. Figure 3As can be seen, the temperature of the heat-conducting material 9 exhibits a strong correlation with the incident laser power and the optical power meter reading. Based on the temperature and optical power meter reading change curves of the heat-conducting material 9 within a certain incident laser power range, the data processor 8 can adjust the incident laser power in real time based on the real-time feedback from the optical power meter and the real-time incident laser power, using fuzzy PID control theory to ensure that the heat-conducting material 9 remains constant within the target temperature range. This proves that the passive active temperature control mechanism of the heat-conducting material 9 is safe and effective.

[0039] The raw material composition of the thermally conductive material 9 of the present invention, by weight, is as follows: W A V B O2@SiO2 6~9 parts, carbon nanotubes 0.5~1.5 parts, polymethyl methacrylate 58~61 parts, copper foam 30~32 parts, where 0≤A<B<1.

[0040] To further achieve the objective of this invention, preferably, the method for manufacturing the thermally conductive material 9 of this invention includes the following steps: A1. Take appropriate amounts of ammonium metavanadate powder and ammonium metatungstate powder and disperse them in deionized water solution. Stir and dissolve at 80℃ for 1 hour to obtain solution 1.

[0041] A2. Slowly add oxalic acid powder to solution 1, continue stirring and dissolving at 80℃ for 1 hour, then sonicate for 10 minutes to obtain solution 2.

[0042] A3. Transfer solution 2 to a hydrothermal reactor and react at 250℃ for 24 hours. After removal, centrifuge at 8000 rpm / min for 10 minutes, wash the precipitate with acetone, and dry it at 60℃ under nitrogen for 12 hours. Then anneal at 500℃ for 6 hours to obtain powder 1.

[0043] A4. Disperse an appropriate amount of powder 1 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0044] A5. Add 1 wt% aminosilane coupling agent to the dispersion. Adjust the pH of the solution to 4 by adding glacial acetic acid dropwise. Disperse ultrasonically for 1 hour, then react at 60℃ for 6 hours. After centrifugation, washing, and drying, obtain powder 2.

[0045] A6. Disperse an appropriate amount of powder 2 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0046] A7. Adjust the pH of the solution to 9 by adding ammonia dropwise, slowly add an appropriate amount of tetraethoxysilane solution, react at 50°C for 12 hours, centrifuge, wash and dry to obtain powder 3.

[0047] A8. Take an appropriate amount of carbon nanotubes and disperse them in a sulfuric acid / nitric acid mixed solution (3:1). Disperse them ultrasonically for 1 hour and stir for 24 hours. Then add deionized water to dilute and wash until pH=7. Dry them under vacuum at 60℃ for 12 hours to obtain powder 4.

[0048] A9. Mix an appropriate amount of powder 4 with thionyl chloride and react at 60°C for 24 hours. Then add triethylenetetramine and react at 100°C for 24 hours. After washing with ethanol, dry under vacuum at 60°C for 12 hours to obtain powder 5.

[0049] A10. Place appropriate amounts of polymethyl methacrylate powder, powder 3 and powder 5 into acetone solution, sonicate for 1 hour to mix, and then stir for 2 hours to obtain solution 3.

[0050] A11. Pour solution 3 into the mold, and simultaneously place 10ppi copper foam of the same volume as the mold cavity into the cavity. Place the mold in a vacuum oven and dry at 50°C for 24 hours to obtain the thermally conductive material.

[0051] It should be noted that the thermally conductive material 9 of the present invention has adaptive temperature control properties. When the thermally conductive material 9 is in a low-temperature state, W A V B O2@SiO2 exhibits high penetration, allowing the laser to directly irradiate the carbon nanotubes within the thermally conductive material 9. Upon absorbing the laser energy, the carbon nanotubes rapidly heat up, subsequently transferring the heat to the target body 1 and continuing to propagate into the surrounding tissue. When the temperature of the thermally conductive material 9 exceeds W... A V B Temperature threshold of O2@SiO2, W A V B O2@SiO2 exhibits high reflectivity, reflecting laser energy and preventing further heating of the thermally conductive material 9, thus protecting the tissue from overheating. To verify the effectiveness of the thermally conductive material 9's properties in practical applications, relevant material properties were input into the COMSOL numerical simulation software and a simulation was performed. Figure 4 The image shown is a model diagram from this COMSOL numerical simulation, where the needle is a disposable laser thermotherapy target and the sphere is a simulated tumor tissue. Figure 5 This is a comparison of temperature curves showing the materials with and without adaptive temperature control properties under constant laser irradiation of 0.1W, 0.3W, and 0.5W for 5 minutes. It can be seen that the material without adaptive temperature control exhibits a significantly higher temperature rise than the material with adaptive temperature control under different laser powers, and this difference becomes increasingly pronounced with increasing laser power. However, in the presence of thermally conductive material 9, the highest temperature points of the temperature curves induced by 0.3W and 0.5W lasers are similar, both near the cutoff temperature of thermally conductive material 9 at 68℃. Figure 6This is a comparison of the temperature curves at the highest point on the surface of the laser thermotherapy target head under constant laser irradiation of 0.1W, 0.3W, and 0.5W for 5 minutes, comparing materials with and without adaptive temperature control properties. It can be seen that since the temperature at the surface of the laser thermotherapy target head is transferred from the thermally conductive material 9, the relevant temperature rise difference is... Figure 5 Similarly, as the laser power increases, the temperature rise difference at the surface of the target head with heat-conducting material 9 is small, further demonstrating the limiting effect of heat-conducting material 9 on the temperature of the laser thermotherapy target head, effectively avoiding local overheating in the thermotherapy area. In summary, it can be effectively demonstrated that heat-conducting material 9 has a strong limiting effect on the temperature rise of the target head, stabilizing the center temperature of the laser thermotherapy target head at around the cutoff temperature of heat-conducting material 9, 68°C, effectively proving that the passive temperature control mechanism of the laser thermotherapy target head of the present invention is safe and effective.

[0052] Furthermore, the laser reflection channel 10 is part of the dual-cavity fiber 2, mainly serving as a channel for reflecting laser light, and is connected to the optical power meter 5.

[0053] Furthermore, the laser incident channel 11 is part of the dual-cavity fiber 2, mainly serving as the channel for incident laser light, and is connected to the laser emitter 6.

[0054] The laser thermotherapy target head of this invention operates as follows: Before operation, the laser emitter 6 and optical power meter 5 are connected to the dual-cavity optical fiber 2 via fiber optic coupler 3, thus achieving pre-installation of the disposable laser thermotherapy target head. After medical professionals locate the tumor position and size using MRI, they can formulate a relevant treatment plan. A puncture sheath is inserted through the epidermis at the tumor location, reaching the center of the tumor. The disposable laser thermotherapy target head is then introduced into the tumor center through the puncture sheath channel. The treatment time is then set according to the tumor size, and laser thermotherapy begins. After treatment, the disposable laser thermotherapy target head is withdrawn along the puncture sheath channel, and hemostasis is performed on the patient's epidermis after removing the puncture sheath. Finally, the connection between the laser emitter 6 and optical power meter 5 is disconnected at the fiber optic coupler 3, completing the entire workflow.

[0055] Since the target body 1 has a limited impact on the function of the present invention, the following three embodiments only consider the thermally conductive material.

[0056] Example 1: The raw material composition of the thermally conductive material 9 in this embodiment, by mass parts, is as follows: 6-9 parts of VO2@SiO2, 0.5-1.5 parts of carbon nanotubes, 58-61 parts of polymethyl methacrylate, and 30-32 parts of copper foam.

[0057] The method for manufacturing the thermally conductive material 9 in this embodiment includes the following steps: B1. Take an appropriate amount of ammonium metavanadate powder and disperse it in a deionized water solution. Stir and dissolve it at 80°C for 1 hour to obtain solution 1.

[0058] B2. Slowly add oxalic acid powder to solution 1, continue stirring and dissolving at 80°C for 1 hour, then sonicate for 10 minutes to obtain solution 2.

[0059] B3. Transfer solution 2 to a hydrothermal reactor and react at 250℃ for 24 hours. After removal, centrifuge at 8000 rpm / min for 10 minutes, wash the precipitate with acetone, and dry it at 60℃ under nitrogen for 12 hours. Then anneal at 500℃ for 6 hours to obtain powder 1.

[0060] B4. Disperse an appropriate amount of powder 1 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0061] B5. Add 1 wt% aminosilane coupling agent to the dispersion. Adjust the pH of the solution to 4 by adding glacial acetic acid dropwise. Disperse ultrasonically for 1 hour, then react at 60℃ for 6 hours. After centrifugation, washing, and drying, obtain powder 2.

[0062] B6. Disperse an appropriate amount of powder 2 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0063] B7. Adjust the pH of the solution to 9 by adding ammonia dropwise, slowly add an appropriate amount of tetraethoxysilane solution, react at 50°C for 12 hours, centrifuge, wash and dry to obtain powder 3.

[0064] B8. Take an appropriate amount of carbon nanotubes and disperse them in a sulfuric acid / nitric acid mixed solution (3:1). Disperse them ultrasonically for 1 hour and stir for 24 hours. Then add deionized water to dilute and wash until pH=7. Dry them under vacuum at 60℃ for 12 hours to obtain powder 4.

[0065] B9. Mix an appropriate amount of powder 4 with thionyl chloride and react at 60°C for 24 hours. Then add triethylenetetramine and react at 100°C for 24 hours. After washing with ethanol, dry under vacuum at 60°C for 12 hours to obtain powder 5.

[0066] B10. Place appropriate amounts of polymethyl methacrylate powder, powder 3 and powder 5 into acetone solution, sonicate for 1 hour to mix, and then stir for 2 hours to obtain solution 3.

[0067] B11. Pour solution 3 into the mold, and simultaneously place 10ppi copper foam of the same volume as the mold cavity into the cavity. Place the mold in a vacuum oven and dry at 50°C for 24 hours to obtain thermally conductive material 9.

[0068] Conclusion of Example 1:

[0069] Example 2: The raw material composition of the thermally conductive material 9 in this embodiment, by mass parts, is as follows: W 0.003 V 0.997 O2@SiO2 6~9 parts, carbon nanotubes 0.5~1.5 parts, polymethyl methacrylate 58~61 parts, copper foam 30~32 parts.

[0070] The method for manufacturing the thermally conductive material 9 in this embodiment includes the following steps: C1. Take an appropriate amount of ammonium metavanadate powder and ammonium metatungstate powder (molar ratio: 4000:1) and disperse them in a deionized water solution. Stir and dissolve at 80℃ for 1 hour to obtain solution 1.

[0071] C2. Slowly add oxalic acid powder to solution 1, continue stirring and dissolving at 80℃ for 1 hour, then sonicate for 10 minutes to obtain solution 2.

[0072] C3. Transfer solution 2 to a hydrothermal reactor and react at 250℃ for 24 hours. After removal, centrifuge at 8000 rpm / min for 10 minutes, wash the precipitate with acetone, and dry it at 60℃ under nitrogen for 12 hours. Then anneal at 500℃ for 6 hours to obtain powder 1.

[0073] C4. Disperse an appropriate amount of powder 1 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0074] C5. Add 1 wt% aminosilane coupling agent to the dispersion. Adjust the pH of the solution to 4 by adding glacial acetic acid dropwise. Disperse ultrasonically for 1 hour, then react at 60℃ for 6 hours. After centrifugation, washing, and drying, obtain powder 2.

[0075] C6. Disperse an appropriate amount of powder 2 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0076] C7. Adjust the pH of the solution to 9 by adding ammonia dropwise, slowly add an appropriate amount of tetraethoxysilane solution, react at 50°C for 12 hours, centrifuge, wash and dry to obtain powder 3.

[0077] C8. Take an appropriate amount of carbon nanotubes and disperse them in a sulfuric acid / nitric acid mixed solution (3:1). Disperse them ultrasonically for 1 hour and stir for 24 hours. Then add deionized water to dilute and wash until pH=7. Dry them under vacuum at 60℃ for 12 hours to obtain powder 4.

[0078] C9. Mix an appropriate amount of powder 4 with thionyl chloride and react at 60°C for 24 hours. Then add triethylenetetramine and react at 100°C for 24 hours. After washing with ethanol, dry under vacuum at 60°C for 12 hours to obtain powder 5.

[0079] C10. Place appropriate amounts of polymethyl methacrylate powder, powder 3 and powder 5 into acetone solution respectively, sonicate for 1 hour to mix, and then stir for 2 hours to obtain solution 3.

[0080] C11. Pour solution 3 into the mold, and simultaneously place 10ppi copper foam of the same volume as the mold cavity into the cavity. Place the mold in a vacuum oven and dry at 50°C for 24 hours to obtain thermally conductive material 9.

[0081] Conclusion of Example 2:

[0082] Example 3: The raw material composition of the thermally conductive material 9 in this embodiment, by mass parts, is as follows: W 0.006 V 0.994 O2@SiO2 6~9 parts, carbon nanotubes 0.5~1.5 parts, polymethyl methacrylate 58~61 parts, copper foam 30~32 parts.

[0083] The method for manufacturing the thermally conductive material 9 in this embodiment includes the following steps: D1. Take an appropriate amount of ammonium metavanadate powder and ammonium metatungstate powder (molar ratio: 2000:1) and disperse them in a deionized water solution. Stir and dissolve at 80℃ for 1 hour to obtain solution 1.

[0084] D2. Slowly add oxalic acid powder to solution 1, continue stirring and dissolving at 80℃ for 1 hour, then sonicate for 10 minutes to obtain solution 2.

[0085] D3. Transfer solution 2 to a hydrothermal reactor and react at 250℃ for 24 h. After removal, centrifuge at 8000 rpm / min for 10 min, wash the precipitate with acetone, and dry it at 60℃ under nitrogen for 12 h. Then anneal at 500℃ for 6 h to obtain powder 1.

[0086] D4. Disperse an appropriate amount of powder 1 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0087] D5. Add 1 wt% aminosilane coupling agent to the dispersion. Adjust the pH of the solution to 4 by adding glacial acetic acid dropwise. Disperse ultrasonically for 1 hour, then react at 60℃ for 6 hours. After centrifugation, washing, and drying, obtain powder 2.

[0088] D6. Disperse an appropriate amount of powder 2 in an ethanol / water mixed solution (4:1) and ultrasonically disperse for 1 hour.

[0089] D7. Adjust the pH of the solution to 9 by adding ammonia dropwise, slowly add an appropriate amount of tetraethoxysilane solution, react at 50℃ for 12 hours, centrifuge, wash and dry to obtain powder 3.

[0090] D8. Take an appropriate amount of carbon nanotubes and disperse them in a sulfuric acid / nitric acid mixed solution (3:1). Disperse them ultrasonically for 1 hour and stir for 24 hours. Then add deionized water to dilute and wash until pH=7. Dry them under vacuum at 60℃ for 12 hours to obtain powder 4.

[0091] D9. Mix an appropriate amount of powder 4 with thionyl chloride and react at 60°C for 24 hours. Then add triethylenetetramine and react at 100°C for 24 hours. After washing with ethanol, dry under vacuum at 60°C for 12 hours to obtain powder 5.

[0092] D10. Place appropriate amounts of polymethyl methacrylate powder, powder 3 and powder 5 into acetone solution, sonicate for 1 hour to mix, and then stir for 2 hours to obtain solution 3.

[0093] D11. Pour solution 3 into the mold, and simultaneously place 10ppi copper foam of the same volume as the mold cavity into the cavity. Place the mold in a vacuum oven and dry at 50°C for 24 hours to obtain thermally conductive material 9.

[0094] Conclusion of Example 3:

[0095] The above three embodiments, by systematically changing the tungsten doping ratio (from 0 to 0.003 and then to 0.006), clearly demonstrate that adjusting W... A V B The tungsten content in the O2@SiO2 core material allows for precise and continuous control of the thermally induced phase transition temperature of the final composite thermally conductive material (from 68°C to 63°C and 59°C). This directly verifies that the temperature threshold of the thermally conductive material of this invention can be actively designed and customized according to clinical treatment needs (such as safe temperatures for different tissues).

[0096] Example 1 demonstrates the baseline phase transition point of 68°C, while Examples 2 and 3, through low-level tungsten doping, successfully adjusted the phase transition temperature to a range closer to the ideal treatment window (e.g., around 45°C). These results not only demonstrate the physical basis of the passive temperature control mechanism but also fundamentally support the invention's concept of adjustable temperature thresholds, enabling laser thermotherapy to combine robust physical safety protection with flexible adjustment of treatment parameters.

[0097] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications or substitutions are all included within the scope defined by the claims of the present invention.

Claims

1. A thermally conductive material, characterized in that, Includes the following components: W A V B O2@SiO2, carbon nanotubes, polymer matrix and metal foam, where 0≤A<B<1.

2. The thermally conductive material according to claim 1, characterized in that, The components include the following parts by weight: W A V B O2@SiO2 6~9 parts, carbon nanotubes 0.5~1.5 parts, polymer matrix 58~61 parts, metal foam 30~32 parts.

3. The thermally conductive material according to claim 2, characterized in that: The polymer matrix is ​​polymethyl methacrylate; The metal foam is copper foam with a pore density of 5-20 PPI.

4. The method for preparing the thermally conductive material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Carbon nanotubes are acidified to obtain acidified carbon nanotube powder. S2. The acidified carbon nanotube powder is subjected to amination treatment to obtain amination-modified carbon nanotube powder. S3, W A V B O2@SiO2 powder, the amino-modified carbon nanotube powder, polymer matrix raw materials and organic solvent are mixed to obtain a mixed slurry; S4. The mixed slurry is combined with a metal foam skeleton and cured to obtain the thermally conductive material.

5. The preparation method according to claim 4, characterized in that, In step S1, the acidification treatment specifically involves dispersing carbon nanotubes in a mixed acid, ultrasonically treating them for 0.5-2 hours, stirring them at room temperature for 12-36 hours, and then washing and drying them to obtain acidified carbon nanotube powder. The mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of (2-4):

1.

6. The preparation method according to claim 4, characterized in that, In step S2, the amination treatment specifically includes: S2a. The acidified carbon nanotube powder is mixed with thionyl chloride and reacted at 50-70°C for 18-30 hours. S2b, followed by the addition of a polyamine compound, reacted at 80-120℃ for 18-30 hours, and after washing and drying, amination-modified carbon nanotube powder was obtained.

7. The preparation method according to claim 4, characterized in that: In step S3, the organic solvent is one or more of acetone, N,N-dimethylformamide, and tetrahydrofuran; the polymer matrix raw material is polymer powder or polymer precursor. In step S4, the curing is carried out under vacuum or inert atmosphere, the curing temperature is 40-80℃, and the curing time is 12-48 hours.

8. The preparation method according to claim 4, characterized in that, Before step S1, the preparation of W is also included. A V B Step S0 of O2@SiO2 powder preparation specifically includes: S01. Dissolve the vanadium source and the tungsten source in water to obtain a mixed solution; S02. Add a reducing agent to the mixed solution and stir until homogeneous; S03. The mixture obtained in step S02 is subjected to a hydrothermal reaction to obtain a precursor precipitate; S04. The precursor precipitate is washed, dried and annealed to obtain WAVBO2 powder. S05, regarding the W A V B O2 powder is modified with an aminosilane coupling agent on its surface. S06, W after surface modification A V B Using O2 powder as the core, a SiO2 shell is coated onto its surface via the sol-gel method to obtain W. A V B O2@SiO2 powder.

9. The preparation method according to claim 8, characterized in that: In step S01, the vanadium source is one of ammonium metavanadate, vanadium pentoxide, or vanadium oxalate; the tungsten source is one of ammonium metatungstate, tungstic acid, or tungsten trioxide; the molar ratio of vanadium source to tungsten source is (200~12000):(0~1); In step S02, the reducing agent is one of oxalic acid, hydrazine hydrate, or ascorbic acid; In step S03, the temperature of the hydrothermal reaction is 180-280℃, and the reaction time is 12-36 hours; In step S04, the annealing process is carried out in an inert atmosphere or vacuum, the annealing temperature is 400-600℃, and the annealing time is 4-8 hours. In step S05, the surface aminosilane coupling agent modification is carried out under acidic conditions, with a pH value of 3-5, a reaction temperature of 50-70℃, and a reaction time of 4-8 hours. In step S06, the sol-gel method is carried out under alkaline conditions, using tetraethyl orthosilicate as the silicon source, with a reaction pH of 8-10, a reaction temperature of 40-60℃, and a reaction time of 8-16 hours.

10. A laser thermotherapy target head, characterized in that, include: The target head body is provided with a heat-conducting material as described in any one of claims 1-3; A dual-cavity optical fiber, optically connected to the target head body, includes a laser incident channel for transmitting emitted laser light and a laser reflection channel for receiving reflected laser light. A laser emitter is optically connected to the laser incident channel; An optical power meter, optically connected to the laser reflection channel, is used to detect the power of the reflected laser. A data processor, electrically connected to the laser emitter and the optical power meter, is used to control the output power of the laser emitter based on the reflected laser power detected by the optical power meter.